Efektivitas Pelaksanaan Program Rehabilitasi dan Rekonstruksi Sektor Permukiman Pascabencana Gempabumi di Pulau Lombok - Embun Suryani (Universitas Mataram, 2021)
This study aims to evaluate the effectiveness of post-disaster recovery and physical improvement activities and identify obstacles and problems faced. The study was conducted in 5 districts/cities affected by the earthquake on Lombok Island in 2018. The key informants in this study were BPBDs in the affected districts/cities, along with facilitators for each area. Data collection techniques used was interviews and observation. The effectiveness test was carried out based on the 5T standards set by BNPB, namely the right planning, right administration, right budget absorption, right technical specifics and on time. The results of data analysis indicate that the implementation of the Phase I RTG can be categorized as not meeting 5 standards: 1) not